The geomorphology of coastal features between South Sharm and Yanbu in the north to Ras Al-Breika in the south - the western coast of the Kingdom of Saudi Arabia using remote sensing technology - Al-Haisuni, Maram Hilal (Journal of Humanities & Social Sciences, 2025)
The research examined the geomorphological study of coastal phenomena between south of Sharm Yanbu in the north and up to Ras al-Brika to the south, the study gained importance from the diversity of the region by geomorphological phenomena affected by coastal nudity. The study aimed to highlight the study of coastal phenomena, natural factors affecting the formation of the coast, as well as to determine the degrees of human interventions and their impact on the geomorphology of the coast of the study area. To achieve these objectives, the study relied in its methodology on the objective approach by studying the subject of sculpture and anchoring in terms of characteristic, processes and distribution, as well as the analytical approach by analyzing the characteristics of the phenomenon studied, as well as on some methods such as surveying and field monitoring, in addition to the method of analyzing space visuals to monitor human interventions, and working a map of the degrees of this intervention. The study found the concentration of marine genealogy phenomena, in the Sector of Sharm Yanbu, and the Sector of Ras Al-Abbasi, as well as the human interventions and coastal squirts in the sector of the industrial port of Yanbu, and the sector of the industrial city of Yanbu, comes the sector of a miracle marina, the sector of Khor al-Salja, and the sector of Ras al-Brikiya a fertile environment for the diversity of coastal geomorphological phenomena affected by sculpture and marine anchorage. The study also found human influence as a geomorphological agent through human interventions, where by comparing space visuals for the years (1972-2020) it was possible to indicate the extent of changes in the geomorphology of the Coastline by an increase of 4,891 km by a percentage increase of 40.48%. The study also found that the coast of the study area could be classified in terms of the intensity and degree of human interventions to (highly changing coasts, medium-changing coasts, low-change coasts) and each accounted for (50.14%, 4.43%, 45.42%) respectively.